B346 More intrafascial, less intravenous: external oblique intercostal block for rescue analgesia after pancreatoduodenectomy. (11th August 2022) - Strumia, A; Ruggiero, A; Costa, F; Sarubbi, D; Pascarella, G; Longo, F; Gargano, F; Remore, LM; Fattorini, F; Agrò, FE
Abstract : Background and Aims: Even if pancreatoduodenectomy is a demolishing and painful procedure, it remains the only strategy for pancreatic head tumors; unfortunately, the survival rate is about 40% within 5 years 1 . The most common anesthetic strategy is still general anesthesia, with opioid pain control. Methods: A 72-year-old patient with hypertension was diagnosed with a pancreatic head neoformation and underwent pancreatoduodenectomy under general anesthesia and bilateral TAP block. In the recovery room, the patient had NRS 6; after obtaining informed consent, a bilateral external oblique intercostal block was performed. The lateral and anterior cutaneous branches of the spinal nerves are main the target in surgeries performed with a subcostal incision A linear probe positioned between the midclavicular and anterior axillary lines was used, at the level of the sixth rib. The transducer was then rotated to obtain a paramedian sagittal oblique view. 15 mL of 0.5% ropivacaine was injected between the plane of the external oblique and the intercostal muscles bilateral 2 ( Figure 1 ; Figure 2 ). Results: The external oblique intercostal block demonstrated good coverage for subcostal incisions, immediately and after 24 hours. After 1, 3, 6, 12 and 24 hours, the NRS values never overtake 4 on a scale from 0 to 10. Conclusions: The external oblique intercostal block seems to give excellent analgesia for the upper abdominal segments as rescue anesthesia after major abdominal surgery. Probably, together with the tap block, it can be used as a perioperative analgesic technique for pancreatoduodenectomy, decreasing opioid consumption and improving pain control.